Factors Associated with the Public’s Intention to Report Adverse Drug Reactions to Community Pharmacists in the Makkah Region of Saudi Arabia: An Application of the Theory of Planned Behavior - Alsulami FT (Patient Preference and Adherence)
Fahad T Alsulami Clinical Pharmacy Department, College of Pharmacy, Taif University, Taif, 21944, Saudi ArabiaCorrespondence: Fahad T Alsulami, Clinical Pharmacy Department, College of Pharmacy, Taif University, Taif, 21944, Saudi Arabia, Email F.alsulami@tu.edu.saObjective: This study aimed to evaluate the public’s intention to report ADRs to community pharmacists in the Makkah region of Saudi Arabia and to identify the factors influencing this intention, using the TPB as the theoretical framework.Methods: A cross-sectional study was conducted in the Makkah region of Saudi Arabia via a nonprobability sampling method. Data were gathered through an online self-report survey designed to assess the public’s intention to report ADRs to community pharmacists. Multivariate logistic regression analysis was used to examine the influence of three constructs of the TPB on this intention.Results: A total of 452 individuals participated in the study. Approximately 22% of them reported experiencing ADRs in the last six months, but only 21% were aware of the Saudi NPC. Approximately 62% of the participants expressed a strong intention to report ADRs to community pharmacists. The public exhibited a highly positive attitude toward reporting ADRs, alongside high subjective norms and perceived behavioral control. Among the TPB constructs, attitude had the most significant influence on the intention to report ADRs to community pharmacists, followed by subjective norms and perceived behavioral control.Conclusion: This study revealed a strong public intention to report ADRs to community pharmacists in the Makkah region, driven primarily by positive attitudes, supportive subjective norms, and high perceived behavioral control. However, the findings highlight a critical gap in public awareness of the Saudi NPC, with only 21% of participants aware of its existence. These results underscore the importance of targeted initiatives to improve awareness of the Saudi NPC and to leverage positive attitudes and social norms to promote ADR reporting practices effectively.Keywords: adverse drug reactions, pharmacovigilance, reporting, theory of planned behavior, public, Saudi Arabia